Blood oxygen level‐dependent liver MRI: Can It predict microvascular invasion in HCC?. Issue 3 (2nd November 2012) - Jhaveri, Kartik S.; Cleary, Sean P.; Fischer, Sandra; Haider, Masoom A.; Pargoankar, Vivek; Khalidi, Karim; Moshonov, Hadas; Gallinger, Steven
Abstract Purpose: To assess Blood Oxygen Level‐Dependent (BOLD) Magnetic Resonance Imaging (MRI) for noninvasive preoperative prediction of Microvascular Invasion (MVI) in Hepatocellular Carcinoma (HCC). Materials and Methods: In this prospective, institutional review board approved study, 26 patients (21 men and 5 women age range, 34–77 years with mean age of 61 years) with HCC were evaluated preoperatively with liver MRI including baseline and post oxygen (O2) breathing BOLD MRI. Post processing of MRI data was performed to obtain R2* values (1/s) and correlated with histopathological assessment of MVI. Statistical analysis was performed to assess correlation of baseline R2*, post O2 R2* and R2* ratios to presence of MVI in HCC by binary logistic regression analysis. Results: MVI was present in 15/26 (58%) of HCC on histopathology. The mean R2* values ± SD at baseline and post O2 with and without MVI were 35 ± 12, 36 ± 12, 38 ± 10, 42 ± 17. The R2* values between the groups with and without MVI were not significantly different statistically. Conclusion: BOLD MRI is unable to accurately predict MVI in HCC. The noninvasive preoperative MRI detection of MVI in HCC remains elusive. J. Magn. Reson. Imaging 2013;37:692—699. © 2012 Wiley Periodicals, Inc.